Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Resultados Definitivos: Censo 2017 - Instituto Nacional de Estatística - INE (2019)
O Censo foi realizado em todo o País de 1 a 15 de Agosto de 2017.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia